Diabetic Foot Risk Classification at the Time of Type 2 Diabetes Diagnosis and Subsequent Risk of Mortality: A Population-Based Cohort Study - Wang, Zhaonan; Hazlehurst, Jonathan; Subramanian, Anuradhaa; Tahrani, Abd A.; Hanif, Wasim; Thomas, Neil; Singh, Pushpa; Wang, Jingya; Sainsbury, Christopher; Nirantharakumar, Krishnarajah; Crowe, Francesca L. (Frontiers in Endocrinology, 2022)
Abstract Aims We aimed to compare the mortality of individuals at low, moderate and high risk of DFD in the context of newly diagnosed type 2 diabetes, before developing active diabetic foot problem. Methods This was a population-based cohort study of adults with newly diagnosed type 2 diabetes utilising IQVIA Medical Research Data. The outcome was all-cause mortality among individuals with low, moderate and high risk of DFD, and also in those with no record of foot assessment and those who declined foot examination. Results Of 225,787 individuals with newly diagnosed type 2 diabetes, 34,061 (15.1%) died during the study period from 1st January 2000 to 31st December 2019. Moderate and high risk of DFD were associated with increased mortality risk compared to low risk of DFD (adjusted hazard ratio [aHR] 1.50, 95% CI 1.42, 1.58; aHR 2.01, 95% CI 1.84, 2.20 respectively). Individuals who declined foot examination or who had no record also had increased mortality risk of 75% and 25% vs. those at low risk of DFD, respectively (aHR 1.75, 95% CI 1.51, 2.04; aHR 1.25, 95% CI 1.20, 1.30). Conclusion Individuals with new-onset type 2 diabetes who had medium to high risk of DFD were more likely to die compared to those at low risk of DFD. The associations between declined foot examination and absence of foot examinations, and increased risk of mortality further highlights the importance of assessing foot risk as it not only identifies patients at risk of diabetic foot ulceration but also mortality.